3D-printed fluidic networks for high-power-density heat-managing miniaturized redox flow batteries. Issue 3 (10th February 2017) - Marschewski, Julian; Brenner, Lorenz; Ebejer, Neil; Ruch, Patrick; Michel, Bruno; Poulikakos, Dimos
Abstract : Miniaturized redox flow cells with net power densities of 0.99 W cm −2 using tapered and multiple-pass fluidic networks. Abstract : The miniaturization of redox flow cells (RFCs) paves the way to novel energy conversion concepts combining power delivery and heat regulation. Envisioning the integration of high-power-density RFCs into electronic devices such as microprocessors, lasers, or light-emitting diodes for the purpose of providing power and heat management simultaneously, we introduce and investigate interdigitated, tapered multiple-pass microfluidic networks in miniaturized flow cells. Employing 3D-printing for the facile and inexpensive fabrication of these networks, we demonstrate RFCs with maximum power densities of up to 1.4 W cm −2 at room temperature and net power densities of up to 0.99 W cm −2 after subtracting pumping power losses. The electrolytes employed modest concentrations of 0.4 M K4 Fe(CN)6 and 0.2 M 2, 6-dihydroxyanthraquinone in alkaline electrolyte. We thereby show that rational tailoring of fluidic networks in RFCs is key for the development of devices effectively combining power delivery and thermal management.